Microwave-Assisted Regioselective Synthesis and 2D-NMR Studies of New 1, 2, 3-Triazole Compounds Derived from Acridone. (10th April 2021) - Aarjane, Mohammed; Slassi, Siham; Tazi, Bouchra; Amine, Amina
Abstract : A simple and mild protocol towards the synthesis of new 1, 2, 3-triazole compounds derived from acridone has been developed via regiospecific 1, 3-dipolar cycloaddition reaction between 10-(prop-2-yn-1-yl)acridone derivatives and aromatic azides using CuI as a catalyst. The cycloaddition reaction has been performed using conventional as well as microwave-assisted methods. Microwave-assisted synthesis caused a significant reduction in the reaction times and improvement in the yields of all the synthesized compounds compared with the conventional method. The structure of the 1, 4-disubstituted 1, 2, 3-triazoles has been elucidated by IR, HRMS, 1 H-NMR, 13 C-NMR, and 2D NMR ( 1 H- 13 C HMBC, 1 H- 1 H COSY, and 1 H- 1 H NOESY) spectroscopies.